2016
DOI: 10.1021/acs.jpclett.6b00915
|View full text |Cite
|
Sign up to set email alerts
|

Multistate Density Functional Theory for Effective Diabatic Electronic Coupling

Abstract: Multistate density functional theory (MSDFT) is presented to estimate the effective transfer integral associated with electron and hole transfer reactions. In this approach, the charge-localized diabatic states are defined by block localization of Kohn–Sham orbitals, which constrain the electron density for each diabatic state in orbital space. This differs from the procedure used in constrained density functional theory that partitions the density within specific spatial regions. For a series of model systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 64 publications
1
99
0
Order By: Relevance
“…3,56 The second term in eq 4 is a transition density contribution. 3,18,50,51,56,67 Note that both exchange and static correlation are included in the first term, whereas only dynamic correlation is in the second term. 18 We then approximated the second term of eq 4 by an overlap-weighted average of the KS correlation energies for the two interacting states 50,51 VcTDFfalse[ρABfalse(boldrfalse)false]λ2SABfalse(EcKSfalse[ρAmsfalse(boldrfalse)false]+EcKSfalse[ρBmsfalse(boldrfalse)false]false) where λ is unity in the present work (in later work this parameter or functional could be optimized to fit experimental results), where S AB is the overlap integral ⟨Ψ A |Ψ B ⟩, and where EcKS specifies the correlation energy in the corresponding diagonal matrix element (as obtained from the exchange-correlation functional).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3,56 The second term in eq 4 is a transition density contribution. 3,18,50,51,56,67 Note that both exchange and static correlation are included in the first term, whereas only dynamic correlation is in the second term. 18 We then approximated the second term of eq 4 by an overlap-weighted average of the KS correlation energies for the two interacting states 50,51 VcTDFfalse[ρABfalse(boldrfalse)false]λ2SABfalse(EcKSfalse[ρAmsfalse(boldrfalse)false]+EcKSfalse[ρBmsfalse(boldrfalse)false]false) where λ is unity in the present work (in later work this parameter or functional could be optimized to fit experimental results), where S AB is the overlap integral ⟨Ψ A |Ψ B ⟩, and where EcKS specifies the correlation energy in the corresponding diagonal matrix element (as obtained from the exchange-correlation functional).…”
Section: Methodsmentioning
confidence: 99%
“…We have found that the PBE and PBE0 functionals perform well with the MSDFT method, especially for charge transfer processes. 51,86 …”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…For |H ab |, these include the generalized Mulliken Hush (GMH) method, 14,15 localization and block diagonalization methods, [15][16][17][18][19][20][21] and constrained density functional theory (CDFT). [22][23][24] A more exhaustive list of methods can be found in literature 5,25-33 and we refer the interested readers to these and references therein for a comparison of the different approaches.…”
Section: Introductionmentioning
confidence: 99%